Extraction of Trace Tetracycline by Phase-Separated Sublation - Hou, Yanmin; Zhao, Xiaojun; Xie, Jinmin (Asian Journal of Chemistry, 2015)
As a pretreatment technology, the phase-separated sublation was utilized for the selective extraction and determination of trace tetracycline (TC) in medical wastewater. The results indicated that tetracycline turned into a binary complex (Cu-TC) in the presence of copper(II), which can be separated by phase-separated sublation easily. The extracted binary complex was determined by spectrophotometry. Batch pretreatment tests were carried out, such as the effects of solution pH, reagents dosage, ionic strength, reaction time, floatation time and nitrogen flow rate. The maximum adsorption was 381 nm, phase-separation reagent was 3 mol L-1 sodium chloride, sodium hydroxide solution was acidity regulator and n-propyl alcohol was solvent. Linear regression equation was A = 1.611 × 105C-0.011, lower limit of detection (LOD) was 8.1 × 10-7 mol L-1.